Relationship between copper, iron and immune system: Alzheimer’s disease as a clinical model - Costa, Luciana (2014)
The involvement of metals in a wide range of biological pathways, have been previously extensively described. However, during the last decade there has been a surge of interest in the research of the metabolic links between immunological processes, copper (Cu) and iron (Fe) metabolism. Alzheimer’s disease (AD) is the most frequent neurodegenerative disorder affecting up to 15 million individuals worldwide. The distinction between normal aging and AD is a relevant step to combat this disease efficiently. Thus, the identification of biomarkers and genetic factors underlying AD pathology is extremely important. Oxidative injury in the brain, mediated by the imbalance of redox-active metals as Cu and Fe has been recognized to contribute to the pathology of AD. Accumulation of Fe in the brain is a consistent observation in AD. On the other hand, abnormalities in the synthesis of ceruloplasmin (Cp) have been associated with various neurodegenerative diseases. Cp is an oxidase containing 95% of circulating Cu that has been implicated in maintaining Fe homeostasis in the central nervous system and in its protection from Fe-mediated free radical injury. Importantly, the demonstration that Cp acts in concert with Fe transporters during Fe cellular efflux suggest that elucidation of the mechanisms of Fe and Cu trafficking and metabolism within the nervous system may be an important step to understand the pathogenesis of AD. In this presentation, new insights into the putative functional crosstalk between Fe and Cu metabolism in the pathogenesis of AD will be presented. The results obtained by our group and the hypothesis raised during the ongoing research project on this topic will be discussed.